1985
DOI: 10.1111/j.1432-1033.1985.tb09148.x
|View full text |Cite
|
Sign up to set email alerts
|

Turgor-controlled K+ fluxes and their pathways in Escherichia coli

Abstract: Escherichiu coli like most gram-negative bacteria with walls maintains a cytoplasmic osmolarity exceeding that of the medium ; the resulting hydrostatic pressure (turgor pressure) pushes the cytoplasmic membrane against the peptidoglycan and creates a tension in the two envelopes.Potassium is the only cation wich takes part in the regulation of cellular osmolarity. The adaptation of intracellular K ' concentration to external osmolarity involves K + turgor-controlled fluxes. When the medium osmolarity is raise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 24 publications
1
66
1
Order By: Relevance
“…Thus, when the activity of the Prop system was studied in osmo-adapting cells and compared with the activity of the turgor-regulated TrkA system it was found that the Prop system was active when the activity of the TrkA system had subsided ( Fig. 3; see also Meury et al, 1985). Further, Prop activity was unaffected by achievement of steady state accumulation of glycine betaine.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, when the activity of the Prop system was studied in osmo-adapting cells and compared with the activity of the turgor-regulated TrkA system it was found that the Prop system was active when the activity of the TrkA system had subsided ( Fig. 3; see also Meury et al, 1985). Further, Prop activity was unaffected by achievement of steady state accumulation of glycine betaine.…”
Section: Discussionmentioning
confidence: 93%
“…8). However, early experiments to demonstrate activation of K+ efflux by high turgor created by downshock were similarly unsuccessful (Meury et al, 1985). It has been reported that osmotic pressure controls the amount of proline that is excreted into the medium by mutants of S. typhimurium that are osmotolerant due to overproduction of proline (Csonka, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salinity inducible K ϩ uptake and accumulation is the primary signal essential for an overaccumulation of secondary osmolytes, such as glycine betaine or proline, that protect the bacterial systems against salinity stress (Csonka and Hanson, 1991;Meury et al, 1985). Studies on the role of K ϩ as a primary osmolyte in cyanobacterial salinity adaptation have shown that upshock treatment leads to an immediate uptake of Na ϩ during the first 2 min, followed by uptake of K ϩ during the next 20 min, during which Na ϩ is extruded (Reed and Stewart, 1985).…”
Section: ϫ6mentioning
confidence: 99%
“…In Escherichia coli control over K+ accumulation is the major mechanism of turgor regulation (Epstein, 1986) and the size of the cytoplasmic K+ pool is determined primarily by the osmotic pressure of the environment (Epstein & Schultz, 1965). Regulation of both influx and efflux processes for K+ has been demonstrated (Rhoads & Epstein, 1978;Meury et al, 1985;Bakker et al, 1987), which allows the cell to adapt to both low and high turgor. K+ uptake is accomplished by at least three systems, Kdp, Kup and Trk (Bossemeyer et al, 1989a;Epstein, 1986).…”
Section: Introductionmentioning
confidence: 99%